Academic Procrastination and Achievement Motivation - Sugito, Clarissa; Siaputra, Ide Bagus (ANIMA Indonesian Psychological Journal, 2012)
The purpose of this research is to test the Temporal Motivation Theory (TMT) by correlating academic procrastination and achievement motivation on psychology students. Subjects were every psychology student of University of Surabaya from generation 2008 to 2011, focusing on those who were still active on the first semester of the 2011/2012 study term (N = 518). Data were collected with three instruments: Aitken Procrastination Inventory (API), Achievement Motivation Inventory (AMI) (short version), and the Utilitas Tugas (UT) Inventory. Results show a negative corellation between academic procrastination and achievement motivation (r = - .481). One of the aspects of achievement motivation, the task-related motivation, is found to be the root of relation between academic procrastination and achievement motivation. Tujuan penelitian ini adalah menguji Temporal Motivation Theory (TMT) dengan mengorelasikan prokrastinasi akademik dan motivasi berprestasi pada mahasiswa psikologi. Subjek adalah mahasiswa psikologi Universitas Surabaya dari angkatan 2008 hingga 2011, terfokus pada mereka yang masih aktif pada semester gasal tahun akademik 2011/2012 (N = 518). Data dikumpulkan melalui penggunaan tiga instrumen: Aitken Procrastination Inventory (API), Achievement Motivation Inventory (AMI) (versi singkat), dan Angket Utilitas Tugas (UT). Hasil menunjukkan adanya korelasi negatif (r = - .481). Salah satu aspek motivasi berprestasi, yaitu motivasi terkait-tugas, ditemukan menjadi sumber adanya hubungan antara prokrastinasi akademik dan motivasi berprestasi.